2009 technology review and predictions for 2010 - Serrano-Cobos, Jorge (Anuario ThinkEPI, 2010)
Throughout 2009 we have seen a number of technology trends that according to the views of most analysts will have a greater role in 2010. Growth and centralization of social networks, the explosion (and future decline?) of communication and real-time search, the proliferation of cloud services, SaaS and virtualization, the emergence of social software applied to Enterprise 2.0, the growing OS war in the cloud, increased internet access using mobile devices, and the emergence of other technologies at home and away, from 3D to augmented reality. Finally, we consider whether we´ll see in 2010 the beginning of the "death of the website concept".